Relationship between grain yield per spike and components with respect to morphological characters of the stem at maturity in two wheat cultivars (Triticum aestivum L.) (Semiárida, 2020)
Relationships at maturity between culm yield and its components (number of fertile spikelets, number of kernels per spikelet, mean dry weight of one kernel) are studied within the cultivars - Bordenave Puán S.A.G. y Victoria INTA wheats. The morphological characters considered are the dry weight (of leaves, sheats and culm) and length (of spike, culm and its sections). Both cultivars showed high dependence between culm yield and the number of kernel per spike. Victoria lNTA showed dependence between number of kernel per spike and number of kernel per spikelet. Results are analyzed with simple correlation, multiple regression and stepwise regression. Morphological characters are not closely related to that the spike were. The most related to that the spike were. The most related with yields are dry weight of sheath of first uppermost or second leaf.